A Distinct Class of High Peak‐Current Lightning Pulses Over Mountainous Terrain in Thunderstorms. Issue 14 (23rd July 2021) - Lyu, Fanchao; Cummer, Steven A.; Krehbiel, Paul R.; Rison, William; Bruning, Eric C.; Rutledge, Steven A.
Abstract: Cloud‐to‐ground strokes, narrow bipolar events, and energetic in‐cloud pulses are known classes of high peak‐current lightning processes that occur in thunderstorms. Here, we report one more distinct class of high peak‐current events observed exclusively over mountainous terrain, usually above 2, 000 m altitude, in the continental Unites States. These events, which we call mountain‐top energetic pulses (MEPs), are bipolar pulses with negative radiated field polarities. MEPs are generated between the high mountain tops and compact overhead thunderclouds. Evidence supports the hypothesis that MEPs are produced by terrain‐initiated upward positive leaders propagating in high electric fields due to the proximity of the low negative charge regions of the thunderstorms. This scenario further suggests the possibility that MEPs are associated with downward terrestrial gamma‐ray flashes, and their high peak currents imply that they may produce elves. Plain Language Summary: Several distinct classes of high peak‐current lightning processes are known to occur in thunderstorms, such as cloud‐to‐ground (CG) strokes, narrow bipolar events (NBEs), and the recently revealed energetic in‐cloud pulses (EIPs). Here, we report on another type of high‐amplitude event that is generated almost always over mountainous terrain in the western United States. We term them mountain‐top energetic pulses, or MEPs, which produce only radiated fields of negative polarity. The low‐frequency radio waveform characteristics, associated lightning flash structures, as well as weather radar images of the storms suggest that MEPs occur during the propagation of upward, terrain‐initiated, positive polarity lightning leaders. MEPs seem to require several conditions, namely a high ground altitude, a relatively short distance between the ground and overhead cloud, and terrain that can enhance the local electric field. MEP‐producing processes are very different from CGs and NBEs but are similar to EIPs. It is known that positive EIPs are always or almost always associated with upward‐propagating terrestrial gamma‐ray flashes (TGFs). We conjecture that MEPs may be associated with downward‐propagating TGFs. And because of the transient high‐amplitude‐radiated electromagnetic fields, MEPs may also produce ionospheric optical emissions in the form of elves. Key Points: Document a type of highly energetic, negative field polarity lightning processes in the United States only over mountain areas (>2, 800 MSL altitude) Measurements indicate that these pulses occur during the upward propagation of terrain‐initiated positive leaders Their similarity to other processes suggests that they may be associated with terrestrial gamma‐ray flashes and elves